Using camera traps to examine distribution and occupancy trends of ground-dwelling rainforest birds in north-eastern Madagascar. Issue 4 (24th April 2017) - MURPHY, ASIA J.; FARRIS, ZACH J.; KARPANTY, SARAH; KELLY, MARCELLA J.; MILES, KATHLEEN A.; RATELOLAHY, FÉLIX; RAHARINIAINA, RAYMOND P.; GOLDEN, CHRISTOPHER D.
Summary: Camera trap surveys are a non-invasive way to monitor wildlife populations. Although most often used to study medium- and large-sized mammals, camera traps also detect non-target species. These detections provide useful ecological information on little-known species, but such data usually remain unanalysed. We used detections from camera-trapping surveys of native carnivores and small mammals to examine distribution patterns and occupancy trends of little-known ground-dwelling rainforest birds at seven sites across the Masoala-Makira protected area complex in north-eastern Madagascar. We obtained 4, 083 detections of 28 bird species over 18, 056 trap nights from 200 to 2013. We estimated occupancy across the Masoala-Makira protected area complex (hereafter, landscape occupancy) and annual trends in occupancy at three resurveyed sites for five commonly observed species. Landscape occupancy across Masoala-Makira ranged from 0.75 (SE 0.09; Madagascar Magpie-robin Copsychus albospecularis ) to 0.25 (SE 0.06; Scaly Ground-roller Geobiastes squamiger ). Ground-dwelling forest bird occupancy was similar at forest sites that ranged from intact to fully degraded; however, three species were detected less often at sites with high feral cat trap success. Nearly half of all focal species showed declines in annual occupancy probability at one resurveyed site (S02) from 2008 to 2013. The declines in ground-dwelling bird occupancy could have community-wide consequences as birds provide ecosystem services such as seed dispersal and pest regulation. We suggest immediate conservation measures—such as feral cat removal—be implemented to protect ground-dwelling forest birds and other threatened taxa across this landscape.